Has the credit default swap market lowered the cost of corporate debt? - Adam B. Ashcraft; Jo\~ao A. C. Santos (Federal Reserve Bank of New York, 2007)
There have been widespread claims that credit derivatives such as the credit default swap (CDS) have lowered the cost of firms' debt financing by creating for investors new hedging opportunities and information. However, these instruments also give banks an opaque means to sever links to their borrowers, thus reducing lender incentives to screen and monitor. In this paper, we evaluate the effect that the onset of CDS trading has on the spreads that underlying firms pay at issue when they seek funding in the corporate bond and syndicated loan markets. Employing matched-sample methods, we find no evidence that the onset of CDS trading affects the cost of debt financing for the average borrower. However, we do find economically significant adverse effects to risky and informationally-opaque firms. It appears that the onset of CDS trading reduces the effectiveness of the lead bank's retained share in resolving any asymmetric information problems that exist between a lead bank and non-lead participants in a loan syndicate. On the plus side, we do find that CDS trading has a small positive effect on spreads at issue for transparent and safe firms, in which the lead bank's share is much less important. Moreover, we document that the benefit of CDS trading on spreads increases once the market becomes sufficiently liquid. In sum, while CDS trading has contributed to the completeness of markets, it has also created new problems by reducing the effectiveness of lead banks' loan shares as a monitoring device—thus creating a need for regulatory intervention.
Keywords: G24; G32; 330; credit default swaps; loan spreads; credit spreads; Finanzderivat; Credit Default Swap; Kreditversicherung; Verbindlichkeiten; USA